2018
DOI: 10.1097/jsm.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist-Led Physical Activity Interventions Are Efficacious at Increasing Physical Activity Levels: A Systematic Review and Meta-analysis

Abstract: Clinic-based PLPA interventions delivered in private practice, primary care, and outpatient settings were efficacious at increasing PA in adults at risk of NCDs. Improvements did not last long term and were not enhanced with longer interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 57 publications
3
35
0
2
Order By: Relevance
“… Risk of bias was assessed using the Quality Assessment Tool for Before-After (Pre-Post) Studies with No Control Group [ 15 , 16 ] DLCO Diffusing capacity of the lungs for carbon monoxide, FRC Functional residual capacity N/A Not available, not reported in the study …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Risk of bias was assessed using the Quality Assessment Tool for Before-After (Pre-Post) Studies with No Control Group [ 15 , 16 ] DLCO Diffusing capacity of the lungs for carbon monoxide, FRC Functional residual capacity N/A Not available, not reported in the study …”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias was assessed using the Quality Assessment Tool for Before-After (Pre-Post) Studies with No Control Group [ 15 , 16 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…My PhD comprised studies that identified: (1) the efficacy of physiotherapist-led physical activity (PA) interventions; (2) the behaviour change techniques (BCTs), or individual strategies, Australian physiotherapists use to promote PA to improve general health (non-treatment physical activity [NTPA]) and (3) the factors influencing their decision to promote NTPA 1–5…”
Section: What Did I Do?mentioning
confidence: 99%
“…I completed two systematic reviews that found physiotherapist-led NTPA interventions can increase patient PA levels in the short term only 1. Additionally, I found that physiotherapists use fewer BCTs when promoting NTPA in clinical compared with experimental settings,2 suggesting that physiotherapists might use few BCTs to change PA behaviour in practice.…”
Section: How Did I Do It?mentioning
confidence: 99%